2014
DOI: 10.1038/leu.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

A role for oleoylethanolamide in chronic lymphocytic leukemia

Abstract: Oleoylethanolamide (OEA) is a bioactive lipid that stimulates nuclear and G protein-coupled receptors and regulates appetite and fat metabolism. It has not previously been shown to have a role in cancer. However, a mass spectrometry-based lipidomics platform revealed the presence of high amounts of OEA in the plasma of chronic lymphocytic leukemia (CLL) patients compared with normal donors. CLL cells produced OEA and the magnitude of plasma OEA levels was related directly to the circulating leukemic cell numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…PPAR-α is also closely associated to the metabolism of fatty acid amides. For example PPAR-α agonist oleoylethanolamide was observed to be significantly high in patients such that its plasma concentration was directionally related to the number of circulating leukemic cells [47]. In that study, it was suggested that oleoylethanolamide is produced in CLL cells as a lipolytic factor that later plays a role in drug resistance as well as cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-α is also closely associated to the metabolism of fatty acid amides. For example PPAR-α agonist oleoylethanolamide was observed to be significantly high in patients such that its plasma concentration was directionally related to the number of circulating leukemic cells [47]. In that study, it was suggested that oleoylethanolamide is produced in CLL cells as a lipolytic factor that later plays a role in drug resistance as well as cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, monounsaturated and saturated FAEs (e.g., oleoylethanolamide and palmitoylethanolamide) are agonists for peroxisome proliferator-activated nuclear receptors (PPAR-α) (Fu et al, 2003) and G protein-coupled receptors (GPR119 and GPR55) (Godlewski et al, 2009). Oleylethanolamide regulates satiety, body weight, and cancer cell proliferation (Piomelli, 2013; Masoodi et al, 2014); palmitoylethanolamide serves as an early stop signal that contrasts the progress of inflammation (Solorzano et al, 2009). On the other hand, polyunsaturated FAEs (e.g., anandamide) activate cannabinoid receptors (CBs) – the same G protein-coupled receptors targeted by the psychotropic component Δ 9 -tetrahydrocannabinol in marijuana – and contribute in important ways to the regulation of food intake, stress and pain response, and synaptic function (Kathuria et al, 2003; Hohmann et al, 2005; Di Marzo and Matias, 2005; Di Marzo, 2008; Piomelli and Sasso, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxisome proliferator activated receptor (PPAR) could be activated by fatty acid amides and was thought to aid in leukemic cell survival against cytotoxic stressors such as chemotherapeutic drugs [ 28 ]. For example, oleoylethanolamide, an endogenous PPAR-α agonist, was significantly high level in the plasma of chronic lymphocytic leukemia patients such that its plasma concentration was directionally related to the number of circulating leukemic cells [ 29 ]. In that study, it was suggested that oleoylethanolamide was produced by leukemic cells as a lipolytic factor to fuel their growth with a potential role in drug resistance and cancer cachexia [ 29 ], which could give an clue to the physiological functions of dodecanamide, decanamide, and oleamide in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oleoylethanolamide, an endogenous PPAR-α agonist, was significantly high level in the plasma of chronic lymphocytic leukemia patients such that its plasma concentration was directionally related to the number of circulating leukemic cells [ 29 ]. In that study, it was suggested that oleoylethanolamide was produced by leukemic cells as a lipolytic factor to fuel their growth with a potential role in drug resistance and cancer cachexia [ 29 ], which could give an clue to the physiological functions of dodecanamide, decanamide, and oleamide in this study. This was the possible reason that the AML patients with a low level of dodecanamide have better chemosensitivity than those with a high level of dodecanamide.…”
Section: Discussionmentioning
confidence: 99%